The link between socio-economic factors and multiple child deprivations in Kenya - Isaiah Kiprono Byegon; Jane Kabubo-Mariara; Anthony Wambugu (Cogent Economics & Finance, 2021)
This paper analyzes the socio-economic correlates of multiple child deprivations in Kenya using the 1993-2014 KDHS. Conventionally, child well-being is examined from the perspective of income poverty. However, numerous studies have argued that income is just one of the defining characteristics of poverty. Furthermore, examining child well-being only through monetary lens risk leaving behind millions of children because children are not economic agents. Despite global recognition of the importance of having a comprehensive measure of child well-being, there is a dearth of literature on multiple child deprivations. This study utilized data on seven child-specific dimensions of well-being. First, we counted the number of dimensions each child was deprived and then ranked them from those who were not deprived to those who are deprived in four or more dimensions. Second, we examined the distribution of multiple child deprivations by various characteristics. Finally, we investigated factors associated with multiple child deprivations using an ordered logit regression model. The results reveal that rural children, male children and children living in households without access to electricity and under female headship, on average, suffer higher incidence of multiple deprivations than their counterparts. Children with higher birth orders, twins and from rural residence had higher probability of suffering multiple deprivations while higher maternal education, employment of the respondent were associated with lower chances of a child suffering multiple deprivations. The findings of the study suggest the need for integrated policies targeting multiple forms of deprivation and strategies to ensure access to public services in remote areas.
Keywords: I31; I32; J13; 330; child poverty; correlates; Kenya; multidimensional deprivation; ordered logit model